2016
DOI: 10.1038/ncomms10472
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted neurons integrate into adult retinas and respond to light

Abstract: Retinal ganglion cells (RGCs) degenerate in diseases like glaucoma and are not replaced in adult mammals. Here we investigate whether transplanted RGCs can integrate into the mature retina. We have transplanted GFP-labelled RGCs into uninjured rat retinas in vivo by intravitreal injection. Transplanted RGCs acquire the general morphology of endogenous RGCs, with axons orienting towards the optic nerve head of the host retina and dendrites growing into the inner plexiform layer. Preliminary data show in some ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
130
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(150 citation statements)
references
References 46 publications
8
130
4
2
Order By: Relevance
“…Emerging therapeutic interventions intended to restore vision in glaucoma patients, such as RGC transplantation [178] and artificial retinal implants [120], will need to consider the condition of the posterior visual pathway as a confounding factor in the efficacy of therapeutic interventions, including the extent of regeneration of the brain’s visual centres in response to reanimation of the anterior visual pathway [141]. The observation of glaucomatous neurodegeneration in the brain also has implications for assessing the efficacy of neuroprotective therapies, suggesting that the focus of these therapies should be extended to include the whole CNS and that the visual centres of the brain should be included as endpoints in studies of therapeutic efficacy in glaucoma trials [141].…”
Section: Techniques For Monitoring Retinal Ganglion Cell Healthmentioning
confidence: 99%
“…Emerging therapeutic interventions intended to restore vision in glaucoma patients, such as RGC transplantation [178] and artificial retinal implants [120], will need to consider the condition of the posterior visual pathway as a confounding factor in the efficacy of therapeutic interventions, including the extent of regeneration of the brain’s visual centres in response to reanimation of the anterior visual pathway [141]. The observation of glaucomatous neurodegeneration in the brain also has implications for assessing the efficacy of neuroprotective therapies, suggesting that the focus of these therapies should be extended to include the whole CNS and that the visual centres of the brain should be included as endpoints in studies of therapeutic efficacy in glaucoma trials [141].…”
Section: Techniques For Monitoring Retinal Ganglion Cell Healthmentioning
confidence: 99%
“…14 Photoreceptor generation from hESCs has progressed more rapidly than has generation of RGCs. 94,95 Whilst hESC technology is in essence still embryonic, with ethical and scientific challenges, it has the potential to revolutionalize the management of ocular neurodegenerative disease considered incurable through neuroregeneration of functioning retinal neurons. 49 Preclinical studies (in mature uninjured rat and monkey eyes) have previously demonstrated the ability of retinal cells derived from hESCs to survive, integrate into the host retina and mediate light responses.…”
Section: Human Embryonic Stem Cellsmentioning
confidence: 99%
“…Successful transplantation of RGCs has been reported (MacLaren et al, 2006;Venugopalan et al, 2016). RGCs receive visual information from photoreceptors via two intermediate neurons: bipolar and amacrine cells.…”
Section: Takahisa Suzuki | Keita Oochi | Satoko Hakeda-suzuki | Takasmentioning
confidence: 99%